HUBUNGAN ANTARA AKTIFITAS FISIK DAN MANAJEMEN STRES PADA MAHASISWA FISIOTERAPI - Rosintan Napitupulu (Jurnal Fisioterapi dan Rehabilitasi, 2021)
Improving the level of public health is the noble ideal of the country in every development plan both for the long and short term. Doing physical activity that is right and according to age will have an impact on physical, mental and social health. Good stress management on a person will have a positive impact, both for physical and social health in the community. This study aims to determine the relationship and the level of relationship between physical activity variables and stress management in physiotherapy students. This study uses a descriptive correlative research design, with a sample of 108 students covering semesters one, three and six who attended and filled out the questionnaire at a predetermined time (accidental sampling). Data on healthy behavior of students was taken using the HPLP-II questionnaire. Data analysis using the SPSS program by finding the average value of the variable physical activity and stress management which then performed a statistical correlation test of two variables. Results: the average physical activity value was 1,960 and stress management was 2,486. Correlation test is worth 0.994 which means that the two variables have a high relationship. The conclusion of this study is that the lower the physical activity a person does, the lower the stress management. Relationship between physical activity and stress management of students Physiotherapy has a high relationship (perfect association).